HUBUNGAN PENGETAHUAN PASIEN DI KLINIK BAPI KRIAN TERHADAPPENGGUNAAN SUPPOSITORIA PERIODE APRIL 2021 - andri priyoherianto (AFAMEDIS, 2022)
Suppositories are solid pharmaceutical dosage forms that are administired rectally, generally, in the form of a torpedo and melt at body temperature. Lack of knowledge and education about suppository preparations is an important factor that affects the knowledge possed bythe general public on the use of suppostories. The research method used is by distirbuting questionnaires to patient who come to the BAPI Krian clinic with certain predetermained criteria. Using descriptive correlation method which is used toreveal the correlation relationship between variables. And the data analysis used the chi-square correlationtechnique with SPSS version 26.0 tool. The result showed that there was no significant relationshipbetween patient knowledge and how to use suppositories.Keywords: Suppository, Knowledge, Application, Patient, Descriptive Correlation,Relevancy, Chi-square.